Beyond the Theoretical Impasse: Extending the applications of Transactional Distance Theory - Gokool-Ramdoo, Sushita (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
The premise of this article is that the Transactional Distance Theory (TDT) should be accepted as a global theory for the further development of distance education. Despite the fact that a transactional approach seems to be consciously or unconsciously adopted by theorists and practitioners alike, the reluctance to recognise it as a global theory has plunged distance education into a theoretical impasse from whence there has not been much development. It is argued that the TDT can have applications along all the supply chain of the distance education enterprise: it can explicate and ensure the sustainability of quality distance education in a technology-driven world, and; encapsulate the national concerns for policy development. TDT is seen as a useful instrument that should effectively inform institutional as well as national development.